2022
DOI: 10.7759/cureus.24939
|View full text |Cite
|
Sign up to set email alerts
|

Knee-Spine Syndrome: Management Dilemma When Knee Osteoarthritis Coexists With Spine Degeneration

Abstract: The elderly present with progressive degenerative osteoarthritis of the knee and lumbar spine degeneration (LSD). The coexistent conditions when presented concurrently become challenging for the clinicians and surgeons, as well as determining the predominant source of the underlying pain generation factor. The concurrent presentation of a significant knee and low back pain poses challenges in decision-making for treatment with management being normally individualized. The review narrates the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…23 The concurrent presence of OA with spinal pathologies is a recognized clinical challenge. 4,7 Although similar molecular pathways have been documented 24,25 , our research is the first to uniquely demonstrate that this association exists independent of age, and thus underlying factors are more relevant in this co-occurrence than previously understood.…”
Section: Clinical Case Seriessupporting
confidence: 66%
See 2 more Smart Citations
“…23 The concurrent presence of OA with spinal pathologies is a recognized clinical challenge. 4,7 Although similar molecular pathways have been documented 24,25 , our research is the first to uniquely demonstrate that this association exists independent of age, and thus underlying factors are more relevant in this co-occurrence than previously understood.…”
Section: Clinical Case Seriessupporting
confidence: 66%
“…4,5 Moreover, knee OA has been linked with spine diseases under the term "knee-spine syndrome," and these three conditions combined, resulting in "knee-hip-spine syndrome," have been proposed more recently. 6,7 Both phenomena, OA of the lower extremities and spinal degeneration, are age-related changes that share other risk factors such as body mass index (BMI) and sex. [8][9][10] Although they share common demographic risk factors, a study by Prather et al 11 found a higher-than-expected co-occurrence of hip OA and spinal degeneration in patients undergoing total hip replacement according to billing codes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining such postural compensations demands higher energy expenditure than maintaining a normal posture. Over the long term, this may contribute to chronic back pain, an elevated risk of falls, or secondary osteoarthritis of the knees [20].…”
Section: Discussionmentioning
confidence: 99%
“…Lower extremity malalignment syndrome, or knee-hip-spine syndrome (KHSS), is a prevalent musculoskeletal ailment that affects a large number of people [1]. It is typified by aberrant lower extremity alignment, which results in a variety of postural abnormalities, such as discomfort in the knees, hips, and spine [2]. Affected people may find it difficult to carry out everyday tasks and maintain an active lifestyle as a result of these symptoms, which can have a significant negative influence on their quality of life.…”
Section: Introductionmentioning
confidence: 99%